Effectiveness of Logistics Information System Use and Logistics Information System Quality on User Performance through User Satisfaction - Revina Revina; Nofrisel Nofrisel; Zaenal Abidin (Jurnal Impresi Indonesia, 2024)
The effective use of information systems in logistics companies will assist company management in changing business growth strategies. Information system quality is a measurement that focuses on the output processed by the system. This study aims to determine the effectiveness of using the Logistics Information System and its impact on performance and user satisfaction. The research method uses a quantitative approach. The research was conducted at Puninar Logistics with a sample size of 100 employees. Data was collected through a questionnaire with a Likert scale model that had been tested. The data analysis method used is SmartPLS (Partial Least Square) 4.0. The effectiveness of the Logistics Information System cannot be separated from information systems and information technology. The presence of information technology systems has had a lot of influence on an individual/ organization, not only on individuals/ organizations, but this influence extends to business processes and organizational transactions. In addition, effectiveness is a very important concept in organizations because it is a measure of the success of the organization in achieving its goals. This means that it can be said that effectiveness is directly related to achieving goals and is the key to the success of an organization. Research on the effect of information system effectiveness on employee performance has been carried out in many previous studies, but there are inconsistencies in research results regarding this relationship. Research results such as in research show that the effectiveness of the use of information systems has a positive effect on employee performance.